2002
DOI: 10.4049/jimmunol.168.6.2773
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role for CD40 Ligand Interactions in T Lymphocyte-Mediated Modulation of the Murine Immune Response to Pneumococcal Capsular Polysaccharides

Abstract: Protection against infection with pneumococci is provided by anti-capsular polysaccharide (caps-PS) Abs. We investigated whether CD40 ligand (CD40L) plays a role in T lymphocyte-mediated regulation of the immune response to caps-PS, which are considered thymus-independent Ags. Administration of MR1, an antagonist mAb against murine CD40L, in BALB/c mice immunized with Pneumovax resulted in an inhibition of the IgM and IgG Ab response for various caps-PS serotypes. Evidence for the involvement of CD4+ T lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 43 publications
(43 reference statements)
2
36
0
Order By: Relevance
“…Studies using the TI-2 Ags trinitrophenyl (TNP)-Ficoll or DNP-Ficoll (5-7) and one study using purified caps-PS serotype 6 (8) concluded that the Ab responses to these TI-2 Ags are independent of the CD40-CD40L interaction. By contrast, we more recently found that the Ab response to several caps-PS serotypes, including serotype 6, was dependent on the CD40-CD40L interaction (9,10). This was demonstrated in a murine model by showing that the helper effect of CD4 ϩ T lymphocytes and the inhibitory effect of CD8 ϩ T lymphocytes on the anti-caps-PS immune response in vivo and in vitro was abrogated by MR1, a blocking anti-CD40L Ab (9).…”
mentioning
confidence: 89%
“…Studies using the TI-2 Ags trinitrophenyl (TNP)-Ficoll or DNP-Ficoll (5-7) and one study using purified caps-PS serotype 6 (8) concluded that the Ab responses to these TI-2 Ags are independent of the CD40-CD40L interaction. By contrast, we more recently found that the Ab response to several caps-PS serotypes, including serotype 6, was dependent on the CD40-CD40L interaction (9,10). This was demonstrated in a murine model by showing that the helper effect of CD4 ϩ T lymphocytes and the inhibitory effect of CD8 ϩ T lymphocytes on the anti-caps-PS immune response in vivo and in vitro was abrogated by MR1, a blocking anti-CD40L Ab (9).…”
mentioning
confidence: 89%
“…ELISA for detection of anti-caps-PS antibodies was performed as previously described [10]. For detection of human anti-caps-PS antibodies, peroxidase-conjugated goat-antihuman IgM and goat anti-human IgG in a dilution of 1/5,000 was added to the wells.…”
Section: Elisa For Detection Of Anti-caps-ps Antibodiesmentioning
confidence: 99%
“…IgM antibodies and cytokine-producing cells ELISPOT assay for the detection of anti-caps-PS IgM antibodies was performed as previously described [10]. For detection of IgM-producing cells, alkaline phosphataseconjugated goat anti-human IgG was used.…”
Section: Elispot Assay For the Detection Of Anti-caps-psmentioning
confidence: 99%
See 1 more Smart Citation
“…However, T lymphocytes do modulate the anti-caps-PS antibody response: CD4 + T lymphocytes have a stimulatory effect, whereas CD8 + T lymphocytes have an inhibitory effect [5]. These regulatory effects are dependent on the CD40-CD40L interaction [6,7]. In addition to T lymphocytes, also antigen-presenting cells (APC) seem important in the antibody response to caps-PS.…”
Section: Introductionmentioning
confidence: 99%